The Philosophical Foundations of Human Rights in Islamic Thought - Layla Khalouhen Naout Hussein Al-Agili, Asst. Lecturer (lark, 2026)
The concept of humanity in our religious and traditional texts did not carry the same meanings as it is understood today in our contemporary world, a concept rooted in the European Renaissance, particularly in the ideas of what is known as humanism. There is a near consensus among contemporary Muslims regarding human rights: they follow a single approach, returning to the texts of the Quran and Sunnah as the primary source of these rights. In almost every study presented by a contemporary Islamic thinker on this subject, we find a purpose behind the list of fundamental rights stipulated in modern charters and declarations, along with Quranic verses and Prophetic hadiths indicating that these rights were already recognized in Islam. Since all sacred texts affirm those fundamental ethical principles that humanity has acquired through long experience, and which have been confirmed by philosophy and human wisdom since antiquity, the task of these researchers in finding texts that support basic human rights will not be a difficult one, especially since the generality of religious texts allows for the extraction of multiple and diverse meanings from them. These attempts, which are also achieving remarkable success, are a source of great pride for the contemporary Muslim thinker. It is worth noting that this pride does not stem from a belief that the foundation of human rights in the holy book of Islam is broader than in modern charters, but rather from the fact that those religious texts that affirmed basic human rights are much older than what Western civilization has known.